Modelling the p53/p66Shc Aging Pathway in the Shortest Living Vertebrate Nothobranchius Furzeri - Priami, Chiara (Aging Dis, 2015)
Oxidative stress induced by reactive oxygen species (ROS) increases during lifespan and is involved in aging processes. The p66Shc adaptor protein is a master regulator of oxidative stress response in mammals. Ablation of p66Shc enhances oxidative stress resistance both in vitro and in vivo. Most importantly, it has been demonstrated that its deletion retards aging in mice. Recently, new insights in the molecular mechanisms involving p66Shc and the p53 tumor suppressor genes were given: a specific p66Shc/p53 transcriptional regulation pathway was uncovered as determinant in oxidative stress response and, likely, in aging. p53, in a p66Shc-dependent manner, negatively downregulates the expression of 200 genes which are involved in the G2/M transition of mitotic cell cycle and are downregulated during physiological aging. p66Shc modulates the response of p53 by activating a p53 isoform (p44/p53, also named Delta40p53). Based on these latest results, several developments are expected in the future, as the generation of animal models to study aging and the evaluation of the use of the p53/p66Shc target genes as biomarkers in aging related diseases. The aim of this review is to investigate the conservation of the p66Shc and p53 role in oxidative stress between fish and mammals. We propose to approach this study trough a new model organism, the annual fish Nothobranchius furzeri, that has been demonstrated to develop typical signs of aging, like in mammals, including senescence, neurodegeneration, metabolic disorders and cancer.